Nanotechnology the new horizon - Anon (Universiti Malaysia Perlis (UniMAP), 2012)
International Lecture Series by Prof. Dr. Ali Hussain Reshak: Nanotechnology the new horizon organized by Universiti Malaysia Perlis, 4th May 2012 at Dewan Keikhlasan, KWSP Building, Kangar, Perlis, Malaysia.